Evaluation of dosimetric effects of metallic artifact reduction and tissue assignment on Monte Carlo dose calculations for 125I prostate implants. Issue 9 (4th August 2022) - Assam, Isong; Vijande, Javier; Ballester, Facundo; Pérez‐Calatayud, José; Poppe, Björn; Siebert, Frank‐André
Abstract: Purpose: Monte Carlo (MC) simulation studies, aimed at evaluating the magnitude of tissue heterogeneity in 125 I prostate permanent seed implant brachytherapy (BT), customarily use clinical post‐implant CT images to generate a virtual representation of a realistic patient model (virtual patient model). Metallic artifact reduction (MAR) techniques and tissue assignment schemes (TAS) are implemented on the post‐implant CT images to mollify metallic artifacts due to BT seeds and to assign tissue types to the voxels corresponding to the bright seed spots and streaking artifacts, respectively. The objective of this study is to assess the combined influence of MAR and TAS on MC absorbed dose calculations in post‐implant CT‐based phantoms. The virtual patient models used for 125 I prostate implant MC absorbed dose calculations in this study are derived from the CT images of an external radiotherapy prostate patient without BT seeds and prostatic calcifications, thus averting the need to implement MAR and TAS. Methods: The geometry of the IsoSeed I25.S17plus source is validated by comparing the MC calculated results of the TG‐43 parameters for the line source approximation with the TG‐43U1S2 consensus data. Four MC absorbed dose calculations are performed in two virtual patient models using the egs_brachy MC code: (1) TG‐43‐based Dw, w‐TG 43, (2) Dw, w‐MBDC that accounts for interseed scattering and attenuation (ISA), (3) Dm, m that examines ISA and tissue heterogeneity by scoring absorbed dose in tissue, and (4) Dw, m that unlike Dm, m scores absorbed dose in water. The MC absorbed doses (1) and (2) are simulated in a TG‐43 patient phantom derived by assigning the densities of every voxel to 1.00 g cm −3 (water), whereas MC absorbed doses (3) and (4) are scored in the TG‐186 patient phantom generated by mapping the mass density of each voxel to tissue according to a CT calibration curve. The MC absorbed doses calculated in this study are compared with VariSeed v8.0 calculated absorbed doses. To evaluate the dosimetric effect of MAR and TAS, the MC absorbed doses of this work (independent of MAR and TAS) are compared to the MC absorbed doses of different 125 I source models from previous studies that were calculated with different MC codes using post‐implant CT‐based phantoms generated by implementing MAR and TAS on post‐implant CT images. Results: The very good agreement of TG‐43 parameters of this study and the published consensus data within 3% validates the geometry of the IsoSeed I25.S17plus source. For the clinical studies, the TG‐43‐based calculations show a D 90 overestimation of more than 4% compared to the more realistic MC methods due to ISA and tissue composition. The results of this work generally show few discrepancies with the post‐implant CT‐based dosimetry studies with respect to the D 90 absorbed dose metric parameter. These discrepancies are mainly Type B uncertainties due to the different 125 I source models and MC codes. Conclusions: The implementation of MAR and TAS on post‐implant CT images have no dosimetric effect on the 125 I prostate MC absorbed dose calculation in post‐implant CT‐based phantoms.